PENGARUH PENILAIAN KINERJA, REWARD, DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT. ESHAN PROSPERA ABADI - Hasnun Aisya; Suryanto Suryanto; Herwan Abdul Muhyi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to determine the effect of performance assessment, reward, and punishment on performance at PT Eshan Prospera Abadi Cikarang. The research method used is quantitative. Primary data was obtained through a survey by filling out open and closed questionnaires, as well as unstructured interviews, while secondary data was obtained through literature studies. The population in this study were all employees of PT Eshan Prospera Abadi, which were 47 respondents. The sampling technique in this study was total sampling. The data analysis technique used was using validity test analysis, reliability test, classical assumption test, determination coefficient test, multiple regression analysis, and correlation coefficient test in finding the effect between performance assessment (X1), reward (X2), and punishment (X3) on performance (Y). The results of this study stated that there was a positive effect between performance assessment, reward, and punishment on performance